Population genetic structure of hard clam (Meretrix lyrata) along the Southern coast of Thailand - JUTHAMAS SUPPAPAN; PRADIT SANGTHONG; , APIRAK SONGRAK; VERAKIAT SUPMEE (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Suppapan J, Sangthong P, Songrak A, Supmee V. 2021. Population genetic structure of hard clam (Meretrix lyrata) along the Southern coast of Thailand. Biodiversitas 22: 2489-2496. The hard clam (Meretrix lyrata), which is an economically important fishery item in Southern Thailand, has decreased rapidly due to overexploitation. To construct sustainable management of this species, genetic information is necessary. In our study, the genetic diversity of M. lyrata was investigated based on the variation of the nucleotide sequence (439 bp) of mitochondrial DNA (mtDNA) in the cytochrome oxidase subunit I gene (mtDNA COI). The mtDNA COI sequences of 145 individuals collecting from 6 sampling sites along the Southern coast of Thailand were analyzed. The results revealed that M. lyrata populations showed moderate to low levels of genetic diversity. All of the population genetic structure analysis revealed the genetic differentiation of the hard clam between the Gulf of Thailand and the Andaman Sea populations. Based on these results, a genetic structure of the hard clam M. lyrata in Southern Thailand was possibly caused by a disruptive gene flow from the geographic factors by the Thai-Malay Peninsula. The demographic history test revealed that the hard clam living in Southern Thailand had experienced population expansion. This study provided the first genetic information that could be used for conserving the hard clam M. lyrata in Southern Thailand.